Evolution of the Neoproterozoic Kareim Basin, north Arabian – Nubian shield - Haytham Sehsah; Christopher L. Kirkland; Tim E. Johnson; Zaki A. Abdel-Fattah (Scientific Reports)
Abstract The transition to continental collision c. 650 Ma induced the bimodal hypsometry of the Arabian-Nubian Shield (ANS), and triggered the formation of voluminous post-amalgamation basins. The intermontane Kareim Basin is a voluminous post-amalgamation depocenter within the ANS. It comprises a thick siliciclastic fill (~ 7 km thick) that accumulated over tens of millions of years during late Neoproterozoic East African orogeny related to the amalgamation of West and East Gondwana. The basin fill consists of four main facies associations (FA1 to FA4) associated with 11 siliciclastic lithofacies and one volcaniclastic lithofacies, which are interpreted as alluvial fan to lacustrine deposits that accumulated under humid to semi-arid conditions. A conglomerate-dominated lithofacies characterizes proximal alluvial fan deposits (FA1), whereas mid to distal alluvial fan strata are represented by braided stream sandstone-dominated lithofacies and conglomerate (FA2–3). Distal fan deposits are composed mainly of sandstone and fine-grained lacustrine sediments (FA4). Tectonically-induced unconformities separate three depositional stages in the Kareim Basin. The lower stage comprises three sandstone-dominant cycles, locally separated by unconformities. The middle stage of the basin represents a stage of syn-depositional tectonic inversion, consistent with the presence of recycled basal boulders derived from the lower stage, and a divergence in the dominant paleo-current directions. Furthermore, thrust faults, tilted and overturned older strata, and the first occurrence of material derived locally from Pan-African volcanic rocks (the Dokhan Volcanic Suite) and basement gneiss domes are additional clues for the syn-depositional tectonic inversion. The upper stage comprises conglomerate-dominant cycles, and represents the transition to post-collisional extension and rapid subsidence. Detrital zircon U–Pb ages constrain the syn-depositional inversion of the basin to later than c. 635 Ma, likely coinciding with the onset of collision between West with East Gondwana.